2021
DOI: 10.5144/0256-4947.2021.216
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of flexible fiberoptic laryngoscopy in patients with stridor: a cross-sectional study in a tertiary care pediatric center in Saudi Arabia

Abstract: BACKGROUND: Successful evaluation of a patient with stridor requires a thorough history and physical examination followed by a flexible fiberoptic laryngoscopy (FFL), which provides visualization of the upper airway. OBJECTIVES: Estimate the prevalence of causes of stridor in children who underwent FFL and compare different age groups. Find any significant associations between symptoms and laryngoscopic findings. Identify patients who needed further eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Common indications for bronchoscopy in neonates include unexplained cyanosis, unexplained respiratory distress, and prolonged di culty in withdrawal (9,10). In this study, the top two clinical indications were dyspnea (42.9%) and laryngeal tinnitus (39.3%), which is consistent with the ndings of many studies (11,12). Several studies have con rmed that dyspnea and laryngeal tinnitus are common clinical manifestations of developmental malformations of the respiratory tract in neonates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Common indications for bronchoscopy in neonates include unexplained cyanosis, unexplained respiratory distress, and prolonged di culty in withdrawal (9,10). In this study, the top two clinical indications were dyspnea (42.9%) and laryngeal tinnitus (39.3%), which is consistent with the ndings of many studies (11,12). Several studies have con rmed that dyspnea and laryngeal tinnitus are common clinical manifestations of developmental malformations of the respiratory tract in neonates.…”
Section: Discussionsupporting
confidence: 88%
“…Wang retrospectively analyzed the bronchoscopic data of 175 infants and children with unexplained dyspnea, suggesting that the etiology of dyspnea varies in different age groups, with respiratory malformations predominating up to 6 months of age and the proportion of respiratory malformations tending to decrease with increasing age (11). A study in Saudi Arabia showed that laryngomalacia in 217 children with laryngeal tinnitus was detected at a much higher rate in the younger age group (< 1 year) than in the older age group (> 1 year) (83% vs 43%, P < 0.001) (12). Therefore, in clinical practice, neonates with unexplained dyspnea and laryngeal tinnitus, who are suspected of having an airway abnormality that cannot be clari ed by imaging, should undergo aggressive bronchoscopy to fully evaluate the airway and help clarify the etiology at an early stage.…”
Section: Discussionmentioning
confidence: 99%